Origen y evolución de las fórmulas de saludo con besar en español - Zieliński, Andrzej (Studia Romanica Posnaniensia, 2019)
The aim of the paper is to analyse two Spanish greeting formulas derivated from the atelic predicate besar las manos (y los pies) ‘to kiss the hands (and feet)’, which, despite their apparent formal resemblance, came to codify totally opposite socio-pragmatic values. Through the systematic search in epistolary texts until the beginnings of the 20th century we will try to find (i) the socio-pragmatic factors that play the most important role in each type of greeting; (ii) the paradigmatic origin of each formula, and (iii) their sociocultural distribution.